Production systems, phenotypic and genetic differentiation of pig genetic resources in Zimbabwe, Malawi and South Africa - Halimani, T. E. (Stellenbosch : Stellenbosch University, 2011)
Thesis (PhD (Animal Sciences))--Stellenbosch University, 2011.